The Institution of the Participatory Budget as a Tool of Local Government Development - Rybińska, Daria (Journal of Finance and Financial Law, 2018)
The participatory budget is considered one of the best tools that takes into account residents’ preferences in the process of managing public funds. It is an instrument that allows residents to co-decide on the direction of spending funds from the local government budget. The article attempts to determine the impact of the participatory budget institution on the development of the local government unit. For this purpose, four editions of the participatory budget of the city of Lodz, conducted in 2013–2016, were analyzed. Particular attention was paid to the budgeting principles, types of executed tasks and directions of spending funds. Finally, the conclusions drawn from the conducted analysis are presented, which confirm that the participatory budget is a tool affecting the development of local self-government.